Robot-assisted closed reduction and navigated fixation for pelvic ring injuries: a focused narrative review of a reduction-fixation-audit framework - En Wu; Feng Gu; Wenkai Zhang; Xiaoyu Li; Ye Liang; Zhanxiao Liu; Shen Liu; Yonghui Liang (Frontiers in Medicine, 2026)
Pelvic ring injuries combine three-dimensional deformity with narrow osseous corridors and proximity to neurovascular structures. Minimally invasive fixation can reduce exposure-related morbidity, but its success remains constrained by the quality of reduction achieved before fixation. This focused narrative review examined CT-based phenotyping and planning, mirror-template reconstruction, robot-assisted fracture reduction (RAFR), navigated percutaneous fixation, and postoperative audit. English- and Chinese-language literature was identified by targeted searches from database inception to May 31, 2026. Evidence was synthesized by study design and maturity; no pooled effect estimate or formal risk-of-bias score was undertaken. The published RAFR literature consists predominantly of model validation, a first-in-human report, small single-center series, and one non-randomized comparison. These studies demonstrate technical feasibility and early radiographic acceptability in selected fresh unstable pelvic ring injuries. A 2024 series extends direct but still preliminary evidence to displaced fragility fractures. Recruitment centers, investigators, and enrollment periods overlap across several reports, so cohort independence cannot be assumed. Reported reductions in blood loss, incision length, radiation exposure, or early functional scores should therefore be treated as associations rather than proof of comparative effectiveness. Long-term safety, durable function, learning curve, multicenter reproducibility, and cost-effectiveness remain unestablished. The main contribution of this review is a surgeon-in-the-loop reduction-fixation-audit framework that separates four endpoints: technical feasibility, radiographic reduction, clinical effectiveness, and safety. It also proposes candidate reporting domains and distinguishes evidence-informed early-use scenarios from investigational applications. Force-controlled stress testing for equivocal instability remains a research hypothesis, not an established indication.